MEASURING THE IMPACT OF PHILANTHROPY IN ISLAMIC EDUCATION: METHODOLOGY AND INDICATORS (CASE STUDY: ISLAMIC BOARDING SCHOOLS IN BANTEN) - Mulyadi, Rasad; Moch Faisal; Abidin Nasyar; Ahmad Qurtubi; Ali Muhtarom (Cakrawala Pedagogik, 2026)
Measuring the Impact of Philanthropy in Islamic Education: Methodology and Indicators (Case Study: Islamic Boarding Schools in Banten). This study aims to measure the impact of philanthropy in Islamic education, particularly in Islamic boarding schools in Banten. By using appropriate methodology, this study is expected to provide a clear picture of the contribution of philanthropy in improving the quality of education and the welf are of students. Based on data obtained from various studies, including reports from the Islamic Education Foundation (YPI) and educational research institutions, we found that philanthropic investment can significantly improve student learning out comes.The results of this study also found that the social impact of philanthropy in Islamic education is very significant. Programs that focus on community empowerment, such as skill straining for students' parents, not only improve children's education but also improve the overall family economy.